Sabil Al-Hikmah Claim Management System - NASWAN, DANIEL; Ruhaya Ab Aziz (Applied Information Technology And Computer Science, 2025)
This project aims to modernize the process of claiming free meals at Universiti Tun Hussein Onn Malaysia (UTHM) by replacing the manual, paper-based system with a robust digital solution. Inefficiencies, inaccuracies, and delays in the existing system affect students, administrators, and vendors, necessitating a more streamlined approach. The proposed system integrates QR code technology, a mobile application, and a centralized web-based platform to facilitate efficient meal tracking, real-time data management, and transparent claim processing. Security features such as login authentication, data encryption, and role-based access controls ensure data integrity and user safety. Designed for UTHM’s campus environment, the system targets eligible students, administrators, and approved vendors, enhancing operational workflows and reducing manual workload. Upon completion, the project will deliver a secure, efficient, and transparent solution that minimizes errors, reduces delays, and supports timely reimbursements, aligning with UTHM’s commitment to student welfare and technological advancement.